Coexistence Of Rengasdengklok's Economic Dualism From The Japanese Occupation To The Modern Era - Hidayatullah, Raza Syarif; Basith, Syahirul; Putra, Raka Dania; Arista, Rizky Dwi; Putri, Inggrid Merryana (International Journal Labs, 2025)
This research analyzes economic dualism in Rengasdengklok from the Japanese colonial period to the modern era, using a historical approach to explore the socio-economic changes. The research methods include heuristics for historical data collection, source criticism to evaluate information validity, data interpretation in a socio-economic context, and historiography to compile a systematic narrative. Economic dualism reflects the existence of two different systems-traditional and traditional, operating simultaneously. During the colonial period, Dutch colonial policy emphasized exploiting resources for export, while the Japanese focused on production for military needs. The results show that while the modern sector is thriving, the traditional sector remains the main foundation of local communities. This dualism creates challenges of inequality and dependence on modern markets but also presents opportunities for tradition-based innovation. The implications of this research emphasize the importance of inclusive policies that integrate the traditional and modern sectors for sustainable economic development.